EFEKTIVITAS PENYALURAN ZAKAT PRODUKTIF DALAM MEMBERDAYAKAN EKONOMI MUSTAHIQ : Studi Program Bantuan Modal Usaha di BAZNAS Kota Depok - Azizah Khoirotun Nisa (2022)
Productive Zakat is defined as a method of giving zakat that allows mustahik to be involved in productive activities by growing their finances through productive activities. productive zakat can be empowered as business capital where zakat funds given to mustahiq are used for productive activities to increase their business. at BAZNAS Depok City in 2020 1 billion rupiah was used for the utilization of zakat from a total distribution of 3.8 billion. This study aims to identify the effectiveness of productive zakat distribution in empowering the mustahiq economy in the study of business capital assistance programs at BAZNAS Depok City. The research method uses descriptive qualitative methods with a case study approach, namely the BAZNAS business capital assistance program in Depok City. The results showed that the distribution of productive zakat as business capital carried out by BAZNAS Depok City had been running effectively because it had fulfilled four indicators of the effectiveness of the program's targeting, program objectives, program socialization, and program monitoring.